THE EXPRESSION OF ALPHA-SMOOTH MUSCLE ACTIN IN CONTRACTED SOCKET - Dwiamelia, Theresia; Respatika, Datu; Darajati, Irene Titin; Dibyasakti, Banu Aji; Utomo, Purjanto Tepo; Supartoto, Agus (Majalah Oftalmologi Indonesia, 2023)
Purpose: A contracted socket is considered a common complication in anophthalmic patients, with the resulting poor fitting of an ocular prosthesis. In severe cases where patients have had multiple previous reconstructive attempts, further socket contraction may result from fibrosis, leading to eventual surgical failure. Alpha-smooth muscle actin (?-SMA) is often used to identify pathologic fibroblasts. It may serve as a reliable marker for myofibroblast cells. The aim of the study was to find ?-SMA protein expression in myofibroblasts derived from orbital socket contracture. Methods: In this study, we observed five patients with contracted sockets who underwent fornicoplasty and buccal graft surgery from October 2022 to February 2023. Tissue samples were taken from the conjunctival fornix area during the surgery and then examined for ?-SMA expression. Result: In this study, there were 2 out of 5 (40%) positive ?-SMA expressions with history of recurrent contraction, 2 (40%) negative expressions with no history of recurrent contraction, and 1 result that could not be assessed due to the limited number of samples containing fibroblasts. Conclusion: ?-SMA levels can be detected in patients with contracted sockets. Patients with a history of recurrently contracted sockets have a tendency to express positive ?-SMA. This may allow for the need for the administration of antimetabolites in patients with recurrent contracted sockets to avoid recurrence of this contracted socket.